Adding photonic entanglement to superradiance by using multilevel atoms - Amir Sivan; Meir Orenstein (Physical Review Research)
We show here that the photonic states emitted by ensembles of multilevel atoms via a superradiance process exhibit entanglement in the modal (frequency) degree of freedom, making this collective emission process a favorable candidate for a fast, bright, and deterministic source of entangled photons. This entanglement is driven by two mechanisms: (i) selective excitation of the atomic ensemble to a superposition state, and (ii) degeneracies of the optical transitions owing to the internal structure of the emitting atoms. The latter induces intricate nonradiative virtual transitions in the ensemble, which create interatomic correlations that are imprinted onto the emitted photons. One of the important outcomes of this complexity is the generation of mode-independent entangled multiphoton states. In addition, we study the dynamics of the correlations of the superradiating multilevel atom ensembles, and demonstrate a case where they exhibit beating in steady state as a result of the aforementioned virtual transitions.